Peroxyl Radicals Modify 6-Phosphogluconolactonase from Escherichia Coli Via Oxidation of Specific Amino Acids and Aggregation Which Inhibits Enzyme Activity - Romero-Figueroa, J; Arenas-Salinas, F (Elsevier Inc., 2023)
6-phosphogluconolactonase (6PGL) catalyzes the second reaction of the pentose phosphate pathway (PPP) converting 6-phosphogluconolactone to 6-phosphogluconate. The PPP is critical to the generation of NADPH and metabolic intermediates, but some of its components are susceptible to oxidative inactivation. Previous studies have characterized damage to the first (glucose-6-phosphate dehydrogenase) and third (6-phosphogluconate dehydrogenase) enzymes of the pathway, but no data are available for 6PGL. This knowledge gap is addressed here. Oxidation of Escherichia coli 6PGL by peroxyl radicals (ROO•, from AAPH (2,2′-azobis(2-methylpropionamidine) dihydrochloride) was examined using SDS-PAGE, amino acid consumption, liquid chromatography with mass detection (LC-MS), protein carbonyl formation and computational methods. NADPH generation was assessed using mixtures all three enzymes of the oxidative phase of the PPP. Incubation of 6PGL with 10 or 100 mM AAPH resulted in protein aggregation mostly due to reducible (disulfide) bonds. High fluxes of ROO• induced consumption of Cys, Met and Trp, with the Cys oxidation rationalizing the aggregate formation. Low levels of carbonyls were detected, while LC-MS analyses provided evidence for oxidation of selected Trp and Met residues (Met1, Trp18, Met41, Trp203, Met220 and Met221). ROO• elicited little loss of enzymatic activity of monomeric 6PGL, but the aggregates showed diminished NADPH generation. This is consistent with in silico analyses that indicate that the modified Trp and Met are far from the 6-phosphogluconolactone binding site and the catalytic dyad (His130 and Arg179). Together these data indicate that monomeric 6PGL is a robust enzyme towards oxidative inactivation by ROO• and when compared to other PPP enzymes. © 2023 Elsevier Inc.